Analysis of the Implementation of ISO 9001:2015 on the Quality of Implementation of Irrigation Network Modernization Projects - Perkasa, Windy Dwi; Sagala, Henrico; Kusumastuti, Aryati Indah; Mulyono, Heri (Ridwan Institute, 2025)
The importance of implementing Quality Management Systems (QMS) in facing business competition in the construction sector, especially at the construction work implementation stage—both private and government—requires strict compliance with quality standards and procedures to produce quality construction products that meet customer expectations and needs. This study analyzes the level and impact of implementing QMS ISO 9001:2015 clauses 4 to 10 on the quality of irrigation network modernization projects in the Rentang Irrigation Area. The research combines descriptive analysis with a quantitative approach, involving 98 respondents from 14 construction service providers directly involved in the project. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression. Results show that the degree of QMS ISO 9001:2015 adoption in the Rentang irrigation network modernization project was very good, with an average score of 4.06 (80.96%). Multiple linear regression analysis and hypothesis testing prove that implementation of clause 7 (support) and clause 10 (improvement) partially have significant effects on project quality. The simultaneous implementation of clauses 4 to 10 of ISO 9001:2015 has a significant impact on the quality of irrigation network modernization project implementation. The effectiveness depends on strong top management support to ensure adequate resources and continuously evaluated employee competencies, guaranteeing construction products meet customer expectations and needs.